Adipose Tissue Development Relies on Coordinated Extracellular Matrix Remodeling, Angiogenesis, and Adipogenesis - Elizabeth K. Johnston; Rosalyn D. Abbott (Biomedicines, 2022)
Despite developing prenatally, the adipose tissue is unique in its ability to undergo drastic growth even after reaching its mature size. This development and subsequent maintenance rely on the proper coordination between the vascular niche and the adipose compartment. In this review, the process of adipose tissue development is broken down to explain (1) the ultrastructural matrix remodeling that is undertaken during simultaneous adipogenesis and angiogenesis, (2) the paracrine crosstalk involved during adipose development, (3) the mechanical regulators involved in adipose growth, and (4) the proteolytic and paracrine oversight for matrix remodeling during adipose development. It is crucial to gain a better understanding of the complex relationships that exist between adipose tissue and the vasculature during tissue development to provide insights into the pathological tissue expansion of obesity and to develop improved soft-tissue reconstruction techniques.